Advantages and Future Prospects of CNC Machines (International Journal of Scientific Trends, 2025)
Technological advancements are driving progress in all sectors, particularly in the mechanical engineering industry. The continuous development of CNC (Computer Numerical Control) machines significantly contributes to increased production volumes in modern manufacturing. This paper explores the CNC machining process, various CNC operations and their required equipment, as well as the advantages and future trends of CNC technology. Additionally, the article highlights key considerations for manufacturers and machine tool users when evaluating CNC machining as the most effective solution for their specific production needs.